PS02.178: THE EFFECT OF INFLAMMATION AND NUTRITIONAL STATUS AND SARCOPENIA ON ESOPHAGEAL CANCER SURGERY. (14th September 2018) - Soma, Daisuke; Yamada, Kazuhiko; Nohara, Kyoko; Yamashita, Satoshi; Wake, Hitomi; Kokudo, Norihiro
Abstract: Background: An inflammation-based prognostic score, the modified Glasgow Prognostic Score (mGPS), has been established as a useful tool for predicting postoperative outcome in patients with cancer. Recently, depletion of skeletal muscle mass (sarcopenia) has been linked to poor outcome in several types of cancers. In this study investigated the relationship between these factors in patients with operable esopahgeal cancer. Methods: Skeletal muscle mass was assessed in 87 patients who underwent esophagectomy from Jan. 2014 to Dec. 2016. The skeletal muscle tissue areas were measured by the ZioStation. The evaluated samples were slices of the third lumbar vertebrae (L3) in the inferior direction. The muscle area normalized by the square of the height (m2) is called the skeletal muscle index (SMI) (cm2/m2). The modified Glasgow prognostic score (mGPS) was measured using C-reactive protein (CRP) and albumin levels (mGPS 2: CRP > 1.0 mg/dL and albumin < 3.5 g/dL; mGPS 1: CRP > 1.0 mg/dL; mGPS 0: CRP ≤ 1.0 mg/dL). Patients were given mGPS- L group(mGPS0)or mGPS- H(mGPS1, 2). Results: The decrease of the skeletal muscle was higher in the mGPS2 than in the mGPS0. The rate of respiratory complications significantly higher in the sarcopenia group than in the non-sarcopenia group ( P  = 0.01). For other complications the differences were not significant. Kaplan-Meier analysis and log-rank test revealed that Sarcopenia and mGPS-H predicted a higher risk of mortality ( P  = 0.0034 and 0.0001). Univariate analyses revealed that the mGPS, Stage and Sarcopenia were associated with mortality. Multivariate analyses using these 3 factors revealed that only mGPS (HR: 3.18; 95% CI: 1.70–8.70; P  = 0.02) and Sarcopenia (HR: 3.39; 95% CI: 1.27–10.6; P  = 0.01) were an independent risk factor of mortality. Conclusion: The mGPS was closely related on the progression of sarcopenia, and both the mGPS-H and Sarcopenia were poor prognostic factor respectively. Disclosure: All authors have declared no conflicts of interest.